LEGAL FUNDAMENTALS OF DEVELOPING IDEOLOGICAL AND IDEOLOGICAL COMPETENCE IN STUDENTS - Khojaev Munis Otaboevich (Scholar Express Journal, 2022)
The article describes the development of ideological and ideological competence in students, an important factor of legal culture, legal consciousness, development of legal culture, approaches to educating future teachers in the spirit of high moral qualities, citizenship, and patriotism
Keywords: Development of professional competence in students; ideological maturity; legal consciousness